IMPLEMENTASI SENSOR MEMS AKSELEROMETER SEBAGAI ALAT PENGUKUR GETARAN PADA TURBIN ANGIN - Fajar Aswin; Zaldy Sirwansyah Suzen (Jurnal Poli-Teknologi, 2019)
Many techniques are available in the market to measure and analyze vibrations caused by rotating machines and the structure of the machine itself, but require expensive resources to identify the problem of damage. Generally these expensive equipment use conventional sensors such as eddy-current sensors, swing coil velocity sensors and piezoelectric transducer sensors to measure vibration. The implementation of a vibration measuring device in the form of an accelerometer sensor with a type of Micro Electro Mechanical System (MEMS) and a signal processing unit (Arduino Mega microcontroller) is used to measure vibrations that occur in small-scale horizontal type wind turbine blades. Experiments were carried out to check the accelerometer's ability to detect vibration response on wind turbine blades with the free vibration position. Then the signal in the form of the time domain will be converted into the frequency domain to get the dominant frequency value of the turbine blade, which is then analyzed to be compared with the B & K VibroPort 80 vibration meter. The experimental results show that the MEMS type accelerometer sensor can be applied to measure the free vibration conditions on wind turbine blades with an error percentage below 6%.